İlköğretim II. kademe öğrencilerinin sosyal becerilerini algılama düzeylerinin incelenmesi - Özbek, İlknur (My University, 2004)
İlköğretim II. kademe öğrencilerinin sosyal becerilerini algılama düzeylerinin incelenmesi konulu bu araştırmada şu soruların cevapları aranmıştır: 1.Öğrencilerin sosyal beceri düzeyleri nedir? 2.Öğrencilerin sosyal beceri düzeyleri kişisel özelliklere göre farklılaşmakta mıdır? 3.Öğrencilerin sosyal beceri düzeyleri sınıf ve cinsiyet değişkenlerine göre farklılaşmakta mıdır? 4.Öğrencilerin sosyal beceri düzeyleri anne eğitim durumu ve cinsiyet değişkenlerine göre farklılaşmakta mıdır? 5.Öğrencilerin sosyal beceri düzeyleri baba eğitim durumu ve cinsiyet değişkenlerine göre farklılaşmakta mıdır? 6.Öğrencilerin sosyal beceri düzeyleri annenin çalışma durumu ve cinsiyet değişkenlerine göre farklılaşmakta mıdır? 7.Öğrencilerin sosyal beceri düzeyleri annenin çalışma durumu ve sınıf değişkenlerine göre farklılaşmakta mıdır? 8.Öğrencilerin sosyal beceri düzeyleri okul türü ve sınıf değişkenlerine göre farklılaşmakta mıdır? 9.Öğrencilerin sosyal beceri düzeyleri okul türü ve cinsiyet değişkenlerine göre farklılaşmakta mıdır? 10.Öğrencilerin sosyal beceri düzeyleri okul öncesi eğitim alıp almama durumu ile cinsiyet değişkenlerine göre farklılaşmakta mıdır? 11.Öğrencilerin sosyal beceri düzeyleri okul öncesi eğitim alıp almama durumu ile sınıf değişkenlerine göre farklılaşmakta mıdır? 12.Öğrencilerin sosyal beceri düzeyleri anne ve babanın birlikte yaşama durumu ile cinsiyet değişkenlerine göre farklılaşmakta mıdır? 13.Öğrencilerin sosyal beceri düzeyleri anne ve babanın birlikte yaşama durumu ile sınıf değişkenlerine göre farklılaşmakta mıdır? 14.Öğrencilerin sosyal beceri düzeyleri sosyo-ekonomik durum ile cinsiyet değişkenlerine göre farklılaşmakta mıdır? 15.Öğrencilerin sosyal beceri düzeyleri sosyo-ekonomik durum ile sınıf değişkenlerine göre farklılaşmakta mıdır? 16.Öğrencilerin sosyal beceri düzeyleri kendilerini derslerinde başarılı bulup bulmama durumu ile cinsiyet değişkenlerine göre farklılaşmakta mıdır? 17.Öğrencilerin sosyal beceri düzeyleri kendilerini derslerinde başarılı bulup bulmama durumu ile sınıf değişkenlerine göre farklılaşmakta mıdır? 18.Öğrencilerin sosyal beceri düzeyleri kendilerini derslerinde başarılı bulup bulmama durumu ile annenin çalışma durumu değişkenlerine göre farklılaşmakta mıdır? 19.Öğrencilerin sosyal beceri düzeyleri kendilerini derslerinde başarılı bulup bulmama durumu ile okul türü değişkenlerine göre farklılaşmakta mıdır? Tarama modeline uygun olarak düzenlenen araştırmanın evrenini 2003-2004 eğitim-öğretim yılında İstanbul ili Anadolu yakasında bulunan tüm resmi ve özel ilköğretim okullarının II. kademesinde okuyan öğrencilerin tümü; örneklemi ise bu evrenden tesadüfi olarak seçilen 360 öğrenci oluşturmaktadır. Veri toplamak amacıyla iki araç kullanılmıştır: 1.Kişisel Bilgiler Formu 2.Özbek-Aydın Sosyal Beceri Ölçeği Verilerin istatiksel analizleri ile ilgili olarak şu teknikler kullanılmıştır: 1.Öğrencilerin sosyal becerilerini algılama düzeylerini belirlemek amacıyla aritmetik ortalama ve standart sapma yapılmıştır. 2.Öğrencilerin sosyal becerilerini algılama düzeylerinin kişisel özelliklerine göre farklılaşma durumunu belirlemek için t-testi ve varyans analizi hesaplamaları yapılmıştır. 3.Amaçlarda belirtilen 3-19. maddeler için iki boyutlu varyans analizi yapılmıştır. Araştırmadan elde edilen bulgular şu şekildedir: ·Öğrencilerin sosyal beceri düzeyleri cinsiyetlerine göre farklılık göstermektedir. Kız öğrencilerin sosyal becerileri, erkek öğrencilere göre daha gelişmiştir. ·Öğrencilerin sosyal beceri düzeyleri okudukları sınıflara göre farklılık göstermektedir. 8. sınıf öğrencilerinin sosyal becerileri, 6. ve 7. sınıf öğrencilerine göre daha yetersizdir. ·Öğrencilerin sosyal beceri düzeyleri annelerinin eğitim durumuna göre farklılık göstermektedir. Annesi ortaokul mezunu olan öğrencilerin sosyal becerileri, annelerinin eğitim durumu lise, üniversite ve lisansüstü olan öğrencilere göre daha yetersizdir. ·Öğrencilerin sosyal beceri düzeyleri babalarının eğitim durumuna göre farklılık göstermemektedir. ·Öğrencilerin sosyal beceri düzeyleri annelerinin çalışma durumuna göre farklılık göstermemektedir. ·Öğrencilerin sosyal beceri düzeyleri okudukları okul türüne göre farklılık göstermemektedir. ·Öğrencilerin sosyal beceri düzeyleri okul öncesi eğitim alma durumuna göre farklılık göstermemektedir. ·Öğrencilerin sosyal beceri düzeyleri kardeş sayılarına göre farklılık göstermektedir. Tek çocuk olan öğrenciler ve 3 kardeş olan öğrencilerin sosyal becerileri, 4 ve daha fazla kardeş olan öğrenciler ile 2 kardeş olan öğrencilere göre daha gelişmiştir. ·Öğrencilerin sosyal becerileri cinsiyetlerine ve kaçıncı çocuk olduklarına göre farklılık göstermektedir. Tek çocuk olan öğrencilerin sosyal becerileri, ortanca ve en küçük çocuk olan öğrencilere göre daha gelişmiştir. ·Öğrencilerin sosyal beceri düzeyleri annelerinin sağ/ ölü olma durumuna göre farklılık göstermektedir. Annesi sağ olan kız öğrencilerin sosyal becerileri annesi sağ olan erkek öğrencilere göre daha gelişmiştir. ·Öğrencilerin sosyal beceri düzeyleri babalarının sağ/ ölü olma durumuna göre farklılık göstermemektedir. ·Öğrencilerin sosyal beceri düzeyleri anne babalarının birlikte yaşama durumlarına göre farklılık göstermemektedir. ·Öğrencilerin sosyal beceri düzeyleri ailelerinin gelir durumlarına göre farklılık göstermemektedir. ·Öğrencilerin sosyal beceri düzeyleri evde anne, baba ve çocuklar dışında yaşayan kişiler olma durumuna göre farklılık göstermemektedir. ·Öğrencilerin sosyal beceri düzeyleri cinsiyetlerine ve kendilerini derste başarılı bulma durumlarına göre farklılık göstermektedir. Derslerinde kendilerini başarılı ve çok başarılı bulan öğrencilerin sosyal becerileri, biraz başarılı bulan ve başarısız bulan öğrencilere göre daha gelişmiştir. Araştırmanın sonuçlarına göre aşağıdaki öneriler yapılabilir: ·Öğrencilerin sosyal becerilerini geliştirmek amacıyla sosyal beceri eğitimi veren gruplar oluşturulabilir. Öğrencilerin sosyal beceri konusundaki eksikleri veya geliştirilecek yönleri belirlenerek grup rehberliği veya bireysel görüşmeler yapılabilir. ·Okullardaki psikolojik danışma ve rehberlik uygulamalarında sosyal beceri eğitimine ilişkin uygulamalara yer verilebilir. ·İlköğretim müfredatı içerisine sosyal becerilerin geliştirilmesine yönelik etkinlikler konulabilir. Böylece öğretmenler hem konunun önemi ve gerekliliği konusunda bilgilendirilecek hem de sosyal becerileri geliştirmeye yönelik etkinliklerle onlara uygulama kolaylığı sağlanacaktır. ·Üniversitelerin eğitim fakültelerinde eğitim gören bütün öğretmen adaylarına lisans ve yüksek lisans programlarında sosyal becerilerle ilgili dersler verilebilir. ·Öğretmenlere hizmet içi eğitim programlarında sosyal beceri öğretimi konusunda bilgi ve beceri kazandırılabilir. ·Engelli bireylerin sosyal yaşama uyum süreçlerini hızlandırmak için özel eğitime muhtaç çocuklar için sosyal beceri eğitimi çalışmalarına ağırlık verilebilir. ·Üniversitelerin özel eğitim bölümlerinde okuyan öğrencilere, engelli bireylerin sosyal becerilerini geliştirmeye yönelik dersler verilebilir. ·Sosyal beceri eğitim çalışmalarının etkisini arttırmak için ailelerde bu konuda bilinçlendirilmelidir. Anne babalara, sosyal becerileri tanıtacak ve onları bilgilendirecek şekilde danışmanlık yapılabilir. ·Öğretmenler ailelere, çocuklarının sosyal becerilerini geliştirmek için evde uygulayabilecekleri çeşitli etkinlikler vererek aileleri yönlendirebilir.

In this research of which the subject is the study of primary school, second grade students' levels of perception of their social abilities the questions below have been tried to be answered: 1.What are the levels of the students in terms of social abilities? 2.Do the levels of social abilities of the students differentiate according to personal characteristics? 3. Do the levels of social abilities of the students differentiate according to variables of class and gender? 4.Do the levels of social abilities of the students differentiate according to variables of educational situation of their mothers and gender? 5.Do the levels of social abilities of the students differentiate according to variables of educational level of their fathers and gender? 6.Do the levels of social abilities of the students differentiate according to variables of occupational situation of their mothers and gender? 7.Do the levels of social abilities of the students differentiate according to variables of occupational situation of their mothers and class? 8.Do the levels of social abilities of the students differentiate according to variables of school-type and class? 9.Do the levels of social abilities of the students differentiate according to variables of school-type and gender? 10.Do the levels of social abilities of the students differentiate according to variables of whether they took any preschool education or not and gender? 11.Do the levels of social abilities of the students differentiate according to variables of whether they took any preschool education or not and class? 12. Do the levels of social abilities of the students differentiate according to variables of whether their parents live together or not and gender? 13.Do the levels of social abilities of the students differentiate according to variables of whether their parents live together or not and class? 14.Do the levels of social abilities of the students differentiate according to variables of socio-economic situation and gender? 15.Do the levels of social abilities of the students differentiate according to variables of socio-economic situation and class? 16.Do the levels of social abilities of the students differentiate according to variables of whether they regard themselves successful in their lessons or not and gender? 17.Do the levels of social abilities of the students differentiate according to variables of whether they regard themselves successful in their lessons or not and class? 18.Do the levels of social abilities of the students differentiate according to variables of whether they regard themselves successful in their lessons or not and the occupational situation of their mothers? 19.Do the levels of social abilities of the students differentiate according to variables of whether they regard themselves successful in their lessons or not and school-type? The context of this research that was organized in accordance with surveillance model consists of all of the second-grade students who studied in state and private primary schools which are located in Anatolian part of İstanbul in 2003-2004 educational year. The samples of the research are 360 students who were selected randomly in this context. Two tools were used to collect data: 1.Personal Information Questionnaires 2.Social Ability Scale of Özbek-Aydın The techniques below were used for the sake of statistical analysis of the data: 1.To designate students' levels of perception of their own social abilities, arithmetic centering and standard deviation were applied. 2.To determine how far students' levels of perception of their own social abilities differentiate according to their personal characteristics, T-Test and calculation of the analysis of variance were applied. 3. For items 13-19 which were stated among purposes, two-dimensioned analysis of variance was applied. Findings of the research are: ·The levels of social abilities of the students differentiate according to their genders. Compared with male students, social abilities of female students are more matured. · The levels of social abilities of the students differentiate according to the classes in which they study. Social abilities of eight-grade students are less matured than the ones of six and seven-grade students. ·The levels of social abilities of the students differentiate according to educational situation of their mothers. Social abilities of the students whose mothers graduated from primary schools are less matured than the ones of those whose mothers had an education in a high school and a university on graduate and postgraduate levels. ·The levels of social abilities of the students don't differentiate according to educational situation of their fathers. ·The levels of social abilities of the students don't differentiate according to occupational situation of their mothers. ·The levels of social abilities of the students don't differentiate according to types of the schools in which they study. ·The levels of social abilities of the students don't differentiate according to whether they took any preschool education or not. ·The levels of social abilities of the students differentiate according to the number of their sisters/ brothers. Social abilities of the students who have got no sisters/ brothers and the ones who have got 2 sisters/ brothers are more matured than the ones of those who have got two, four or more sisters/ brothers. ·The levels of social abilities of the students differentiate according to which in order they are among the siblings in their families. Social abilities of the students who are the only siblings in their families are more matured than the ones of those who are the middle or the youngest children in their families. · The levels of social abilities of the students differentiate according to whether their mothers are alive or dead. Social abilities of female students whose mothers are alive are more matured than the ones of male students whose mothers are alive. ·The levels of social abilities of the students don't differentiate according to whether their fathers are alive or dead. ·The levels of social abilities of the students don't differentiate according to whether their parents live together or not. ·The levels of social abilities of the students don't differentiate according to level of income of their families. ·The levels of social abilities of the students don't differentiate according to whether there is anybody living with their families other than mothers, fathers, brothers and sisters. · The levels of social abilities of the students differentiate according to their genders and whether they find themselves successful in the lessons or not. Social abilities of the students who find themselves very successful in the lessons are more matured than the ones of those who find themselves unsuccessful or a little successful. Such suggestions as below can be made according to research conclusions: ·In order to develop social abilities of the students, some groups to give an education of social ability can be constituted. After deficiencies of the students in terms of social abilities and the ways to overcome these deficiencies are determined, an overall guidance for the group or individual conferences can be organized. ·Some practices about the education of social ability can be integrated into the practices about psychological consultation and guidance which are applied in the schools. ·Some activities to develop social abilities of the students can be placed into the curriculum of primary education. Thus, teachers will be informed about the importance and the necessity of the subject of social ability and the activities to develop social abilities of the students will help teachers in terms of implementation. ·All practice teachers who study in education faculties of universities can be given some education on the development of social abilities in the context of graduate and postgraduate programs. ·Teachers can be informed and educated on the development of social abilities in in-service training sessions. ·With the aim of accelerating the process of adapting to social life of handicapped people, practices to develop social abilities of the children who are in need of special education can be focused on. ·The undergraduate students who are studying in the field of special education can be given some courses devoted to develop social abilities of handicapped people. ·To increase the effect of the education of social ability, families also can be made conscious about this subject. Parents can be provided with consultation, which will introduce and teach social abilities to them. ·Teachers can guide families by giving them different activities they can implement at home to develop social abilities of their children.
Keywords: Eğitim; Okul organizasyonu ve yönetimi; Öğrenci